The Hidden Struggle: Premenstrual Depression its Impact on Women’s Health and Management Strategies: A Narrative Review. - Deepika SN; Syeda Farha S 1 * (International Journal of Nutritions, 2026)
Background: Premenstrual depression, including Premenstrual Syndrome (PMS) and Premenstrual Dysphoric Disorder (PMDD), represents a significant yet underrecognized contributor to women’s mental health burden. Hormonal fluctuations during the luteal phase interact with neurotransmitter systems, particularly serotonin and GABA, leading to affective and somatic symptoms that impair daily functioning. Objective: This systematic review synthesizes evidence on the prevalence, pathophysiology, psychological impact, and management strategies of premenstrual depression among reproductive-aged women, with particular emphasis on Indian populations. Methods: A systematic search of electronic databases, including PubMed, Google Scholar, ScienceDirect, Springer, and related peer-reviewed sources was conducted for studies published between 2015 and 2024. Eligible studies included cross-sectional studies, randomized controlled trials, systematic reviews, and meta-analyses focusing on women aged 20–40 years. Outcomes assessed included depression, anxiety, stress, nutritional status, symptom severity, and therapeutic interventions. Studies involving menopausal women or conducted outside defined criteria were excluded. Results: Reported prevalence of PMS in India ranged from 14.3% to 74.4%, while PMDD prevalence varied from 3.7% to 65.7%. Evidence indicates strong associations between hormonal sensitivity, serotonergic dysfunction, and mood disturbances. Premenstrual depression significantly affects work productivity, academic performance, sleep quality, and overall quality of life. Non-pharmacological interventions—including dietary modification, calcium and omega-3 supplementation, exercise, and yoga—demonstrated symptom reduction. Selective serotonin reuptake inhibitors (SSRIs) remain the gold-standard pharmacological treatment, with additional benefits observed from hormonal therapies. Conclusion: Premenstrual depression substantially impacts women’s psychological and functional well-being. Early diagnosis and individualized, multimodal treatment approaches are essential to improve outcomes and reduce disease burden.
Keywords: Premenstrual depression symptoms; SSRIs; mental health interventions; premenstrual syndrome; serotonin imbalance